Hydrogen-enhanced cracking revealed by in situ micro-cantilever bending test inside environmental scanning electron microscope - Deng, Y.; Hajilou, T.; Barnoush, Afrooz (The Royal Society Publishing, 2017)
© 2017 The Author(s) Published by the Royal Society. All rights reserved. To evaluate the hydrogen (H)-induced embrittlement in iron aluminium intermetallics, especially the one with stoichiometric composition of 50 at.% Al, a novel in situ micro-cantilever bending test was applied within an environmental scanning electron microscope (ESEM), which provides both a full process monitoring and a clean, in situ H-charging condition. Two sets of cantilevers were analysed in this work: one set of un-notched cantilevers, and the other set with focused ion beam-milled notch laying on two crystallographic planes: (010) and (110). The cantilevers were tested under two environmental conditions: vacuum (approximately 5×10-4 Pa) and ESEM (450 Pa water vapour). Crack initiation at stressconcentrated locations and propagation to cause catastrophic failure were observed when cantilevers were tested in the presence of H; while no cracking occurred when tested in vacuum. Both the bending strength for un-notched beams and the fracture toughness for notched beams were reduced under H exposure. The hydrogen embrittlement (HE) susceptibility was found to be orientation dependent: The (010) crystallographic plane was more fragile to HE than the (110) plane.